Why do couples and singles save during retirement? - Mariacristina De Nardi; Eric French; John Bailey Jones; Rory McGee (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2021)
While the savings of retired singles tend to fall with age, those of retired couples tend to rise. We estimate a rich model of retired singles and couples with bequest motives and uncertain longevity and medical expenses. Our estimates imply that while medical expenses are an important driver of the savings of middle-income singles, bequest motives matter for couples and high-income singles, and generate transfers to non-spousal heirs whenever a household member dies. The interaction of medical expenses and bequest motives is a crucial determinant of savings for all retirees. Hence, to understand savings, it is important to model household structure, medical expenses, and bequest motives.
Keywords: 330; Sparen; Rentner; Offenbarte Präferenzen; Erbe; Medizinische Behandlung; Vergleich; Alleinlebende; Ehe; Lebensgemeinschaft; Momentenmethode; USA